Safe and effective delivery of supplemental iron to healthy adults: a two-phase, randomized, double-blind trial – the safe iron study - Lewis, Erin D.; Ortega, Edwin F.; Dao, Maria Carlota; Barger, Kathryn; Mason, Joel B.; Leong, John M.; Osburne, Marcia S.; Magoun, Loranne; Nepveux V, Felix J.; Chishti, Athar H.; Schwake, Christopher; Quynh, Anh; et al. (Frontiers in Nutrition, 2023)
Introduction: The safety of novel forms of iron in healthy, iron-replete adults as might occur if used in population-based iron supplementation programs was examined. We tested the hypotheses that supplementation with nanoparticulate iron hydroxide adipate tartrate (IHAT), an iron-enriched Aspergillus oryzae product (ASP), or ferrous sulphate heptahydrate (FS) are safe as indicated by erythrocyte susceptibility to malarial infection, bacterial proliferation, and gut inflammation. Responses to FS administered daily or weekly, and with or without other micronutrients were compared. Methods: Two phases of randomized, double-blinded trials were conducted in Boston, MA. Phase I randomized 160 volunteers to six treatments: placebo, IHAT, ASP, FS, and FS plus a micronutrient powder (MNP) administrated daily at 60 mg Fe/day; and FS administered as a single weekly dose of 420 mg Fe. Phase II randomized 84 volunteers to IHAT, ASP or FS administered at 120 mg Fe/day. Completing these phases were 151 and 77 participants, respectively. The study was powered to detect effects on primary endpoints: susceptibility of participant erythrocytes to infection by Plasmodium falciparum, the proliferation potential of selected pathogenic bacteria in sera, and markers of gut inflammation. Secondary endpoints for which the study was not powered included indicators of iron status and gastrointestinal symptoms. Results: Supplementation with any form of iron did not affect any primary endpoint. In Phase I, the frequency of gastrointestinal symptoms associated with FS was unaffected by dosing with MNP or weekly administration; but participants taking IHAT more frequently reported abdominal pain (27%, p<0.008) and nausea (4%, p=0.009) than those taking FS, while those taking ASP more frequently reported nausea (8%, p=0.009). Surprisingly, only 9% of participants taking IHAT at 120 mg Fe/day (Phase II) reported abdominal pain and no other group reported that symptom. Discussion: With respect to the primary endpoints, few differences were found when comparing these forms of iron, indicating that 28 days of 60 or 120 mg/day of IHAT, ASP or FS may be safe for healthy, iron-replete adults. With respect to other endpoints, subjects receiving IHAT more frequently reported abdominal pain and nausea, suggesting the need for further study.